2007
DOI: 10.1080/13921657.2007.10512826
|View full text |Cite
|
Sign up to set email alerts
|

PREDATION RATE AND SIZE SELECTIVITY OF THE INVASIVE AMPHIPOD GMELINOIDES FASCIATUS PREYING UPON THE NATIVE ISOPOD ASELLUS AQUATICUS

Abstract: Abstract. Experimental studies were carried out on the predation pressure of the invasive Baikalian amphipod Gmelinoides fasciatus on the native isopod Asellus aquaticus to explain the decrease in the density of this native after a successful establishment of G. fasciatus in many aquatic systems of eastern Europe. Experimental results confirmed that adult males of G. fasciatus preyed upon A. aquaticus. Predation rates of G. fasciatus varied from 0.28 to 1.07 ind. day -¹, depending on prey density, with a maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…Local disappearance of G. lacustris and A. aquaticus may be a result of antagonistic relationships (predation and competition) between these species and G. fasciatus (Berezina et al., 2009). Experimental studies by Pankova and Berezina (2007) confirmed that G. fasciatus being an active predator upon A. aquaticus and may have a strong impact on the density of this isopod in natural habitats. The predation of G. fasciatus causes abrupt changes in the taxonomical composition of benthic communities (Berezina, 2007).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Local disappearance of G. lacustris and A. aquaticus may be a result of antagonistic relationships (predation and competition) between these species and G. fasciatus (Berezina et al., 2009). Experimental studies by Pankova and Berezina (2007) confirmed that G. fasciatus being an active predator upon A. aquaticus and may have a strong impact on the density of this isopod in natural habitats. The predation of G. fasciatus causes abrupt changes in the taxonomical composition of benthic communities (Berezina, 2007).…”
Section: Discussionmentioning
confidence: 85%
“…Amphipods significantly contribute to benthic biomass of different aquatic ecosystems and play an important role in their food webs as a trophic link from primary producers to higher‐order consumers, including fish and birds (Pankova and Berezina, 2007). G. fasciatus was introduced into different aquatic ecosystems of the former USSR with the aim of enhancing food base for fish (Berezina, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The isopod Asellus aquaticus and another amphipod Pallasea quadrispinosa were also subjected to the competition by the invader, reaching high abundances (above 1000 m −2 and 0.5 g m −2 ) only at sites with low G. fasciatus densities (Berezina et al., 2009). It had been experimentally confirmed that the local disappearance of the native crustaceans G. lacustris and A. aquaticus after the establishment of G. fasciatus may have been a result of interspecific interactions, particularly selective predation by the invader (Pankova and Berezina, 2007; Berezina, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The most common non-indigenous species in European large lakes are the zebra mussel Dreissena polymorpha Pallas (Ricciardi, 2003) and the Baikalian gammarid Gmelinoides fasciatus (Stebbing) (Timm & Timm, 1993). The latter is the most active invasive species in Eastern Europe (Pankova & Berezina, 2007). G. fasciatus was introduced in the 1960s and 1970s from the Lake Baikal basin into lakes and reservoirs in the former USSR with the purpose of enhancing fish production (Berezina, 2007).…”
Section: Endemic Endangered and Alien Species In Large Lakesmentioning
confidence: 99%